Analysis of Productivity Dynamics and Shallot Price Fluctuations Viewed from an Islamic Economics Perspective - Waqi'atul Aqidah (LPPM, Universitas Islam Syarifuddin Lumajang, 2024)
This research aims to analyze the dynamics of productivity and fluctuations in shallot prices in Kecamatan Pajarakan, Kabupaten Probolinggo. The method of this research is qualitative method. Data collection was carried out using interviews, observation, and documentation methods. Data analysis techniques include data collection, data reduction, data presentation, and drawing conclusion. The results of this research show that the productivity of shallots produced by farmers is fluctuating dynamic, although in the last few months of 2023 there is an upward trend. This dynamic cause by weather change, pest and disease attacks, plant care and maintenance, and capital adequacy. In line of this, fluctuations in the price of shallots on the market are also quite high. This is due to several factors, namely consumer demand, stock supplies at traders, offers from farmers, the big harvest momet, and the presence of supplies from other sources. The mechanism for determining shallot prices is formed directly in the market. As per the perspective of Islamic Economics in Al Ghazali’s thought, it is called “natural order”, without any intervention by upholding the principles of pleasure, healthy competition, openness and honesty